PENERAPAN KONSEP WATER SENSITIVE URBAN DESIGN TERHADAP PERENCANAAN PERUMAHAN PADA KAWASAN RAWAN BANJIR KECAMATAN PERIUK - Priska Stefani; B. Irwan Wipranata; Regina Suryadjaja; Suryadi Santoso (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Flooding in Periuk Sub-district has been a priority issue for the local government for a long time. Until now, flood control is still an annual work program of several related parties. Meanwhile, the population growth rate of Tangerang City is increasing, so the need for residential land is also increasing over time. As an area planned as an integrated residential area, Periuk Sub-district, which borders directly with Tangerang Regency (Pasarkemis Sub-district), has experienced good progress in the development of residential areas dominated by private developers. However, flood vulnerability is an important consideration in the development of new residential areas, as is the case with the vacant land of the study object between Situ Bulakan and Situ Gelam. With the land designation as housing based on spatial plan (RTRW) Tangerang City 2023, the vacant land has not been optimally utilized because it is included in the flood-prone area. By applying the concept of water sensitive urban design (WSUD), the spatial arrangement of the residential area will focus on water cycle management (Drainage) and public open space as water catchment areas. In addition, adjustments are also made to the requirements for residential development in flood-prone areas to produce recommendations for components that are most suitable for the characteristics of the study object. Keywords: housing planning; water sensitive urban design (WSUD); and flood-prone area Abstrak Kerawanan bencana banjir di Kecamatan Periuk sudah menjadi permasalahan prioritas pemerintah daerah dahulu. Hingga kini, pengendalian banjir masih  menjadi program kerja tahunan dari beberapa instansi atau pihak terkait. Sedangkan laju pertumbuhan penduduk Kota Tangerang semakin meningkat, sehingga kebutuhan akan lahan hunian juga semakin meningkat seiring berjalannya waktu. Sebagai wilayah yang direncanakan sebagai kawasan permukiman terpadu, Kecamatan Periuk yang berbatasan langsung dengan wilayah Kabupaten Tangerang (Kecamatan Pasarkemis) mengalami perkembangan dalam pengembangan kawasan hunian yang cukup baik dan didominasi oleh pengembang swasta. Namun kerawanan bencana banjir menjadi pertimbangan penting dalam pengembangan kawasan perumahan baru, seperti yang terjadi pada lahan kosong objek studi di antara Situ Bulakan dan Situ Gelam. Dengan peruntukan lahan sebagai perumahan berdasarkan RTRW Kota Tangerang tahun 2030, lahan kosong belum dimanfaatkan dengan optimal karena termasuk ke dalam kawasan rawan banjir. Dengan menerapkan konsep water sensitive urban design (WSUD), penataan ruang kawasan perumahan akan difokuskan pada pengelolaan siklus air (Drainase) dan ruang terbuka publik sebagai daerah resapan air. Selain itu juga dilakukan penyesuaian terhadap syarat pengembangan hunian pada kawasan rawan banjir untuk menghasilkan rekomendasi komponen yang paling sesuai dengan karakteristik objek studi.